Gestational diabetes mellitus and linear growth in early childhood - Chen, Zi-Lin; Liu, Xin; Tao, Min-Yi; Yang, Meng-Nan; He, Hua; Fang, Fang; Wu, Ting; Ouyang, Fengxiu; Zhang, Jun; Li, Fei; Luo, Zhong-Cheng (Frontiers in Endocrinology, 2024)
Gestational diabetes mellitus (GDM) is a common pregnancy complication with potential short-and long-term adverse consequences for both mothers and fetuses. It is unclear whether GDM affects linear growth in the offspring; research data are limited and inconsistent. In a prospective birth cohort in Shanghai (n=2055 children; 369 born to mothers with GDM). We sought to evaluate the impact of GDM on longitudinal linear growth in early childhood. Length/height was measured in children at birth, 6 weeks, 6 months, 1, 2 and 4 years of age. Multivariate linear regression and generalized estimating equation models were employed to assess the impact of GDM on length/height for age Z score (LAZ/HAZ). Average birth length was similar in infants of GDM vs. euglycemic mothers. Adjusting for maternal and child characteristics, the children of mothers with GDM had consistently lower LAZ/HAZ compared to children of mothers without diabetes at ages 6 weeks, 6 months, 1, 2 and 4 years. GDM was associated with a 0.12 (95% confidence intervals 0.04-0.21) deficit in LAZ/HAZ in the growth trajectory from birth to age 4 years after adjusting for maternal and child characteristics. GDM was associated with impaired longitudinal linear growth in early childhood. Further studies are warranted to understand the long-term impact on stature and health.